INFLUENCE OF DEMOGRAPHIC FACTORS ON SUPPORT FOR ECOTOURISM DEVELOPMENT IN IMO STATE - Ogbuji, Stanley I. C. (African Journal of Social and Behavioural Sciences, 2021)
This study examined the influence of demographic factors on support for ecotourism development in Imo State. The multiple sampling technique was adopted in the selection of respondents. Data used for the study were obtained through structured questionnaire and observations. A set of structured questionnaire was administered to 360 randomly selected respondents, however, 316 were retrieved. Data obtained were analyzed using descriptive statistics in the form of frequency count, percentage and mean. Results of the demographic characteristics of the respondents showed that there were more males (70%) than females (30%) while age group 31-40 accounts for higher percentage (54%) of the population. Most of the respondents were farmers (52%) and monthly income range of <20000 (36%) was more in the state, while the respondents were able to read and write. On the influence of demographic factors on support for ecotourism development in the state, there was a no significant relationship between gender (p=0.212), age (p=0.145), marital status (p=0.126), occupation (p=1.000)), educational level (p=0.110) and support for ecotourism development in the state. The only significant demographic factor that can influence residents support for ecotourism development in the State is the monthly income (p=0.004). It was concluded that demographic factors have no major association with support for ecotourism development in Imo State except for income. Therefore, the study recommended that since majority of the respondents were subsistent farmers, there is the need to diversify the economy through ecotourism and by making funds available to SMEs in the state in order to improve their income level.